Ethics Codes Of The Hungarian Top 200 Companies - Szeged, Krisztina; Szilágyi, Roland (European Scientific Journal, ESJ, 2016)
The aim of this current article is to summarize the statements regarding the code of ethics examined in the empirical research of the Hungarian TOP 200 corporate ethics institution system. This study was conducted by the Ethics and Transparency work team of the Hungarian Business Leaders Forum. The research indicates that in Hungary, similar to transitional economies, the codes of ethics are also undeveloped. The main purposes of introducing the code of ethics include providing guidelines for employees, declaring ethical commitment, and the development of companyâ€™s culture. Based on the topics, emphasis is laid on protecting the interests of the companies. However, improving competitiveness and meeting the expectations of stakeholders plays an insignificant role. The practice of the code of ethics in the Hungarian large companies contradicts the global tendency that the codes are more and more comprehensive. Thus, they contain several objectives that define corporate responsibility, and they not only focus on the do’s and donâ€™ts of employees.